L‘écriture réflexive comme levier de professionnalisation des enseignants de fle - Bouzidi, Souraya (Vestnik za tuje jezike, 2025)
This paper examines the role of reflective writing in the professionalization of teachers of French as a foreign language (FFL) during initial training. Analyzing 16 practice nar-ratives written by 8 Master’s students in FFL didactics at the University of Khenchela (Algeria), we explore how narrative writing fosters the development of reflective skills despite significant linguistic constraints (A2 level in French). The multidimensional analysis reveals significant progression between the first and the second narrative across five dimensions: deepening of reflection, diversification of analyzed situations, development of reflective posture, mastery of written expression, and narrative creativity. The results demonstrate that the creative approach helps overcome linguistic barriers and constitutes an effective tool for developing a teacher’s professional identity. This study contributes to enriching training devices by proposing an innovative alternative to traditional ap-proaches to practice analysis. The research is grounded in the theoretical foundations of Schön, Dewey, and Perrenoud, and draws on the Vygotskian perspective of writing as cognitive mediation. Our methodology includes qualitative analysis using two comple-mentary grids to evaluate the development of reflexivity and writing competencies. The findings show a 28% improvement in average scores for reflective dimensions, with the most notable progress in practice analysis (a 33% increase) and solution construction (a 35% increase).
Keywords: écriture réflexive; FFL; FLE; formation initiale; initial training; practice narratives; pripovedi o praksah; profesionalizacija učiteljev; professionnalisation enseignante; récits de pratiques; reflective writing; refleksivno pisanje; teacher professionalization; začetno izobraževanje